Eksistensi Toko Tradisional Sejak Berdirinya Alfamart Di Desa Antibar Kecamatan Mempawah Timur Kabupaten Mempawah - Muhammad Ariel Dafa Alvaro; Desca Thea Purnama; Nurwijayanto; Muhklis; Hasanah (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
The social changes that emerge in society in the current era of globalization and the rapid progress and development of technology have an impact on people's lives. This change can also be seen in the market industry, with the big changes that are happening now, there are many modern shops that provide various kinds of human needs so that you can shop for various goods in just one shop. This article describes the influence that Alfamart has had on the existence of traditional shops. This research aims to (1) To find out the existence of traditional shops since the establishment of Alfamart in Antibar Village, East Mempawah District, Mempawah Regency. (2) The research method used is descriptive research with a qualitative approach. The subjects of this research are people who are directly involved in the problem, such as traditional shop owners, the general public who act as consumers and also the head of the Alfamart shop in Antibar Village. The selection of informants was carried out using a purposive sampling technique, while data collection techniques were through observation, interviews and documentation. The theory used in this research is the theory of existence by Zainal Abidin. The results of this research are the decline in the existence of traditional shops in the Antibar Village community since the establishment of Alfamart, which has caused several traditional shops in Antibar Village to switch to selling goods that are not available at Alfamart, there are also shops whose condition is increasingly worrying, such as only providing a few goods, this is of course This alone affects the social life of shop owners whose income is reduced and it is difficult to meet their daily needs.